A Complex of Pleasures: Comment on 'The Pleasure of Art' by Mohan Matthen. Issue 1 (2nd January 2017) - Guyer, Paul
ABSTRACT: Matthen's functionalist account of art and his activity-centred account of aesthetic pleasure are on the right track, but he should recognize the importance of emotional as well as cognitive engagement with art.